Statement by the Managing Director on the Independent Evaluation Office Report on IMF Collaboration with the World Bank on Macro-Structural Issues; June 15, 2020. - International Monetary Fund. Independent Evaluation Office (Washington, D.C. : International Monetary Fund, 2020)
Statement by the Managing Director on the Independent Evaluation Office Report on IMF Collaboration with the World Bank on Macro-Structural Issues.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Monetary Policy; Political Economy